Response surface methodology as a tool for modelling galacto-oligosaccharide production - Vénica, Claudia Inés (2017)
The experiments reported in this research paper describe the effects of β-galactosidase enzyme dose and cheese whey amount, on the maximum concentration and yield of galacto-oligosaccahride (GOS) and reaction time. The experimental plan was based on central composite rotational design (CCRD) and modelled by response surface methodology (RSM). The results indicate that the proposed mathematical models could adequately describe the concentration and yield of GOS and the reaction time within the limits of the factors that are being investigated. The variance analysis shows high values of coefficients of determination (>0.97) while no significant lack of fit was evident. Hence, the models could be employed to select reaction conditions applied in the manufacture of products enriched in bioactive compounds with high value-added.